PENGARUH ANATAR SHOPPING ATTRIBUTE & SHOPPING VALUE TERHADAP BEHAVIORAL INTENTION PADA OBJEK WISATA DI BALI - Yuriko Winarto; Siti Rahayu; Fitri Novika Widjaja (Perpustakaan Universitas Surabaya, 2018)
The purpose of this study to determine and analyze the influence of Shopping Attributr and Shopping Value on the Behavioral Intention. The object is taken shopping outlet in Bali. This study uses primary data by distributing questionnaires to 150 respondents who had been to the island of Bali and shop there. The sampling technique in this study using a non-probability sampling with quantitative approach through statistical testing. Testing using Structural Equation Modeling (SEM) with the help of analysis of moment structures (AMOS 16). The results of this study indicate that the dimension Attribute Shopping has a significant connection to the dimensions of Shopping Value and Shopping Value dimensions has a significant connection to variable Behavioral Intention.